PUBLIC RELATIONS DALAM KEGIATAN MARKETING (Lembaga Penerbitan Universitas Esa Unggul, 2004)
ABSTRACTPublic Relations is the continued process of keying policies, services and actions to the best interest of those individual and groups whose confidence and goodwill an individual or intitution covest, it is the interpretation of these policies, services and actions to assure complete understanding and appreciations. Keywords: Public Relations, Marketing Activities